Integrasi Tradisi dan Inovasi: Kajian Pengembangan Kurikulum Pendidikan Agama Islam di Pesantren, Sekolah dan Madrasah - Hosen Hosen (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The development of Islamic Religious Education Curriculum in Indonesia faces challenges in maintaining the tradition of Islamic scholarship while responding to social and technological developments and the needs of 21st-century competencies. The different characteristics of Islamic educational institutions, such as Islamic boarding schools (pesantren), schools, and madrasahs, require an adaptive curriculum development model without neglecting the Islamic values that form their foundation. This study aims to analyze the characteristics, orientation, and development model of Islamic Religious Education curriculum in Islamic boarding schools (pesantren), schools, and madrasahs, and to identify the forms of integration of tradition and innovation applied in each institution. The study uses a qualitative approach with descriptive-analytical library research. Data were obtained through a review of books, scientific journals, and various relevant literature, then analyzed to describe and compare the development models of Islamic Religious Education curriculum in the three educational institutions. The results show that the development of Islamic Religious Education curriculum in Islamic boarding schools is carried out through the integration of classical Islamic scholarship tradition with digital literacy, project-based learning, and strengthening social competencies. In schools, curriculum development is directed at balancing normative religious goals with student needs through strengthening digital literacy, religious moderation, and active learning. Meanwhile, madrasahs develop curricula by integrating the unique characteristics of Islamic education with the national curriculum through strengthening local religious content, utilizing learning technology, and authentic evaluation. This research contributes to offering a conceptual understanding of a responsive, integrative, and contextual Islamic Religious Education curriculum development model as a basis for developing Islamic education capable of producing a generation of Muslims who are faithful, virtuous, competent, and adaptable to changing times.